Risk Factors Related to Morbidity and Mortality in Geriatric Patients Undergoing Surgical Procedures in Vachira Phuket Hospital - Aroonrat, Walaiporn (Thai Journal of Anesthesiology, 2022)
Background: The Number of Thai citizens aged 65 or older has steadily risen. Thailand will become a full-fledged ageing society in 2021. It is expected that there will be a concurrent rise in the demand for a variety of surgical services in these groups. Older adult patients may have higher perioperative morbidity and mortality during surgery. Safe surgery and safe anesthesia can occur if we identify and manage risk factors related to morbidity and mortality in geriatric patients undergoing surgical procedures. The primary objective was to identify risk factors related to morbidity in geriatric patients undergoing surgical procedures. Material and Method: We retrospectively reviewed 240 anesthetic record forms of adult patients aged more than sixty-four years old who had undergone surgical procedure under anesthesia. Medical records were reviewed for preoperative comorbidity, mode of anesthesia, type of surgical procedure, anesthetic times, estimated blood loss, perioperative morbidity and perioperative mortality within twenty-four hours. Predictors of postoperative complications were first measured using chi-square or Fisher’s exact tests followed by multivariate logistic regression. Results: Two hundred forty patients were studied. The leading cause of morbidity was cardiovascular complication (16.3%); no one died 24 hours postoperative. Multivariate logistic regression analysis showed that anesthetic time was a risk factor related to cardiac complications in geriatric patients undergoing a surgical procedure. Conclusion: No postoperative mortality was observed in geriatric patients undergoing a surgical procedure. Anesthetic time is a risk factor related to cardiac complications in geriatric patients undergoing surgical procedure.